2021
DOI: 10.1186/s12864-021-08007-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and metabolome analysis reveals anthocyanin biosynthesis pathway associated with ramie (Boehmeria nivea (L.) Gaud.) leaf color formation

Abstract: Background The bast fiber crop ramie can be used as high-quality forage resources, especially in tropical or subtropical region where there is lack of high-quality protein feed. Hongxuan No.1 (HX_1) is a unique ramie variety with a light reddish brown leaf color, which is obviously different from elite cultivar, Zhongzhu No.1 (ZZ_1, green leaf). While, the regulatory mechanism of color difference or secondary metaboliates synthesis between these two varieties have not been studied. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 35 publications
(35 reference statements)
1
15
0
Order By: Relevance
“…F3′5′H is an important enzyme that catalyzes the hydroxylation of flavonoids at C3′ and C5′ of ring B, resulting in the production of delphinidin-based anthocyanins [ 23 ]. In this study, undetectable or very low expression of SmF3mr H were observed in A2 and A4 with green and white fruit peel colors, but high expression was found in A1 and A3, followed by A5.…”
Section: Discussionmentioning
confidence: 99%
“…F3′5′H is an important enzyme that catalyzes the hydroxylation of flavonoids at C3′ and C5′ of ring B, resulting in the production of delphinidin-based anthocyanins [ 23 ]. In this study, undetectable or very low expression of SmF3mr H were observed in A2 and A4 with green and white fruit peel colors, but high expression was found in A1 and A3, followed by A5.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of lignin in the treated leaves and stems were supported by multiple previous studies. A study of HCT silence reported the reduction of lignin and increase of various flavonoids [ 26 ]. The inhibition of HCT in tobacco ( Nicotiana benthamiana ) resulted in significant changes in the amount and composition of lignin [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…UHPLC-MS analysis was performed for the methanol extract using ACQUITY UHPLC coupled with Triple TOF 5600 systems in both positive and negative modes, as previously reported [ 69 ], and the details are given in the Supplementary . The tentative constituents were identified by METLIN metabolite and Human Metabolome databases.…”
Section: Methodsmentioning
confidence: 99%